Nicola Sturgeon: A Study of Political Leadership in Scotland: Between Stereotypes and Independence (Politeja, 2025)
This paper provides a multidimensional analysis of Nicola Sturgeon’s political leadership during her tenure as Scotland’s first female First Minister. Drawing on leadership theories, it explores her influence on public policy in key areas such as healthcare, education, gender equality, environmental sustainability, and transportation. The study also examines her pivotal role in advancing Scottish independence and how her media presence and electoral strategies shaped public perception. Additionally, the paper introduces the concept of a regional political leader, using Sturgeon’s leadership style and policy decisions as a framework, particularly in the context of Scottish devolution and nationalist movements.